TFIIA transcriptional activity is controlled by a 'cleave-and-run' Exportin-1/Taspase 1-switch. (10th August 2017) - Schrenk, Christian; Fetz, Verena; Vallet, Cecilia; Heiselmayer, Christina; Schröder, Elisabeth; Hensel, Astrid; Hahlbrock, Angelina; Wünsch, Désirée; Goesswein, Dorothee; Bier, Carolin; Habtemichael, Negusse; Schneider, Günter; et al.
Abstract: Transcription factor TFIIA is controlled by complex regulatory networks including proteolysis by the protease Taspase 1, though the full impact of cleavage remains elusive. Here, we demonstrate that in contrast to the general assumption, de novo produced TFIIA is rapidly confined to the cytoplasm via an evolutionary conserved nuclear export signal (NES, amino acids 21 V INDV RDI FL 30 ), interacting with the nuclear export receptor Exportin-1/chromosomal region maintenance 1 (Crm1). Chemical export inhibition or genetic inactivation of the NES not only promotes TFIIA's nuclear localization but also affects its transcriptional activity. Notably, Taspase 1 processing promotes TFIIA's nuclear accumulation by NES masking, and modulates its transcriptional activity. Moreover, TFIIA complex formation with the TATA box binding protein (TBP) is cooperatively enhanced by inhibition of proteolysis and nuclear export, leading to an increase of the cell cycle inhibitor p16 INK, which is counteracted by prevention of TBP binding. We here identified a novel mechanism how proteolysis and nuclear transport cooperatively fine-tune transcriptional programs.